Motion detection or time-lapse? A comparison of camera trap triggers for monitoring breeding taiga bean geese (Anser fabalis fabalis) - Milaja Nykänen; Hannu Pöysä; Juho Matala; Mervi Kunnasranta (PLoS ONE, 2026)
Game cameras have emerged over the recent years as an effective research tool for collecting various types of data on wild animals, and they are used increasingly also in avian studies. However, choosing the best method to collect data depends on the aim of the research and the characteristics of the target species and its habitat. Here, we compared the performance of two trigger methods of game cameras, passive infrared (PIR) motion sensor and time-lapse triggering, in capturing images of taiga bean goose ( Anser fabalis fabalis ) during two successive breeding seasons in peatlands across Finland in 2020–2021. While accounting for differences in camera effort (difference in the number of hours cameras using different trigger types were operational), we found daily capture probability (probability of at least one goose being present in photos during one day) associated with time-lapse to be marginally higher compared to motion triggered cameras. However, there was no difference in the daily number of geese between the two trigger modes. We also found the daily capture probability and detected number of geese to vary significantly between years, but this could be attributed to random inter-annual variation. In general, we find 15-minute interval time-lapse to be a more suitable method compared to motion triggered cameras to study seasonally elusive ground dwelling birds like the taiga bean goose due to fewer required visits to camera sites and thus less disturbance caused to the birds during the sensitive breeding period. However, using cameras with both trigger types side-by-side would likely lead to best overall capture probability, as indicated by the higher percentage of detection positive time periods when goose detections from both camera types were combined, compared to the percentage derived for either of the trigger types alone.